Intra-pelvic pressure changes after pelvic fracture: A cadaveric study quantifying the effect of a pelvic binder and limb bandaging over a bolster. Issue 4 (April 2017) - Morris, Rhys; Loftus, Andrew; Friedmann, Yasmin; Parker, Paul; Pallister, Ian
Abstract: Introduction: Unstable pelvic fractures can be life-threatening due to catastrophic haemorrhage. Non-invasive methods of reducing and stabilising these injuries include pelvic binder application and also lower limb bandaging over a knee-flexion bolster. Both of these methods help close the pelvic ring and should tamponade bleeding. This study aimed to quantify the intra-pelvic pressure changes that occurred with 3 different manoeuvres: lower limb bandaging over a bolster; a Trauma Pelvic Orthotic Device (T-POD) pelvic binder, and a combination of both. Methods: Following a pilot study with 2 soft embalmed cadavers, a formal study with 6 unembalmed cadavers was performed. For each specimen an unstable pelvic injury was created (OA/OTA 61-C1) by dividing the pelvic ring anteriorly and posteriorly. A 3–4 cm manometric water-filled balloon was placed in the retropubic space and connected to a 50 ml syringe and water manometer via a 3-way tap. A baseline pressure of 8cmH2 O (equating to the average central venous pressure) was used for each cadaver. Steady intra-pelvic pressures (more reliably reflecting the pressures achieved following an intervention) were used in the subsequent statistical analysis, using R statistical language and Rstudio. Paired t -test or Wilcoxon's rank sum test were used (depending on the normality of the dataset) to determine the impact of each intervention on the intra-pelvic pressure. Results: The mean steady intra-pelvic pressures were significantly greater than the baseline pressure for each intervention. The binder and limb bandaging over a bolster alone increased the mean steady pelvic pressures significantly to 24 (SE = 5) (p < 0.036) and 15.5 (SE = 2) (p < 0.02)cmH2 O respectively. Combining these interventions further increased the mean steady pressure to 31 (SE = 7)cmH2 O. However, this was not significantly greater than pressures for each of the individual interventions. Discussion: Both lower limb bandaging over a bolster and pelvic binder application significantly increased intra-pelvic pressure above the baseline pressure. This was further increased through combining these interventions, which could be useful clinically to augment haemorrhage control in these fractures. Conclusion: Lower-limb bandaging over a bolster, and pelvic binder application, both significantly increased intra-pelvic pressures, and were greatest in combination. These findings support the use of these techniques to facilitate non-surgical haemorrhage control.